Forced folding and fracturing induced by differential compaction during post-depositional inflation of sandbodies: Insights from numerical modelling. (February 2020) - Meng, Qingfeng; Hodgetts, David
Abstract: Three series of numerical models based on the discrete element method were constructed to simulate forced folding and fracturing triggered by postdepositional inflation of fluidised sandbody. The models consist of numerous particles that have relatively low to high interparticle bonds to represent overburden sediments with a relatively low to high cohesion, and cohesionless, frictionless particles to represent fluidised sands. The modelling results show that normal faults were produced due to the upward inflation of sand domes and the resulting flexed overburden, when the cohesion of the host sediments is low. Opening voids were created as a result of strata collapse, when the intrusion-related normal faults terminated within the host sediments as blind faults. Conical fractures that are aligned along sandbody margins were produced, which consist of closed, lower segments with a reverse displacement, and opening, middle-upper segments with a minor to zero shear component. Forced folds were generated in most models with a moderate to high cohesion, resulting in differential compaction in the overlying sediments that can account for the formation of fold-related fractures, which are either shear, hybrid or pure tensile, depending on their structural positions. The amplitude of forced folds is closely associated with both cohesion and thickness of sediments in the overburden, whilst fold wavelength is mainly controlled by sediment cohesion. Based on the modelling results, three types of preferential sites for the storage of injected sands were suggested, which are believed to be instructive for subsurface sandbody detection and prediction. This study demonstrates that differential compaction induced by sand inflation can play an important role in overburden folding and fracturing. Highlights: Overburden deformation induced by sandbody inflation was simulated using the discrete element method. A low cohesion of overburden rocks favours formation of normal fault systems above sand domes. Differential compaction due to sandbody inflation can result in shear, tensile and hybrid fractures in the overburden. Sub-horizontal opening-mode fractures induced by sandstone inflation do not necessarily propagate along bedding.